Inside Back Cover: Telluride Misfit Layer Compounds: [(PbTe)1.17]m(TiTe2)n (Angew. Chem. Int. Ed. 22/2014). Issue 22 (15th April 2014) - Moore, Daniel B.; Beekman, Matt; Disch, Sabrina; Johnson, David C.
<x xml:space="preserve">Abstract</x> Much like skiers taking different lifts to different ski runs down a mountain, designed precursors can be used to direct the self‐assembly of targeted intergrowth structures, as described by D. C. Johnson et al. in their Communication on page 5672 ff. The image of Oregon's Mount Hood represents the potential energy landscape, and the colored lines illustrate how different starting points lead to the self‐assembly of different metastable compounds.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>